“What’s in a Name?” A Consensus Proposal for a Common Nomenclature in the Endovascular Resuscitative Management and REBOA Literature - Williams, Timothy K; Johnson, Austin; Neff, Luke; Hörer, Tal M; Moore, Laura; Brenner, Megan; DuBose, Joe; Rasmussen, Todd (Journal of Endovascular Resuscitation and Trauma Management, 2017)
The emerging techniques of REBOA and other Endovascular Trauma Managment (EVTM) concepts has introduced new terminology to the medical vernacular. As research in this fi eld continues, the authors propose a common baseline nomenclature for the initial core essentials of EVTM concepts.